Connectivity of precuneus to the default mode and dorsal attention networks: A possible invariant marker of long-term tinnitus - Sara A. Schmidt; Jake Carpenter-Thompson; Fatima T. Husain (NeuroImage: Clinical, 2017)
Resting state functional connectivity studies of tinnitus have provided inconsistent evidence concerning its neural bases. This may be due to differences in the methodology used, but it is also likely related to the heterogeneity of the tinnitus population. In this study, our goal was to identify resting state functional connectivity alterations that consistently appear across tinnitus subgroups. We examined two sources of variability in the subgroups: tinnitus severity and the length of time a person has had chronic tinnitus (referred to as tinnitus duration). Data for the current large-scale analysis of variance originated partly from our earlier investigations (Schmidt et al., 2013; Carpenter-Thompson et al., 2015) and partly from previously unpublished studies. Decreased correlations between seed regions in the default mode network and the precuneus were consistent across individuals with long-term tinnitus (who have had tinnitus for greater than one year), with more bothersome tinnitus demonstrating stronger decreases. In the dorsal attention network, patients with moderately severe tinnitus showed increased correlations between seeds in the network and the precuneus, with this effect also present in only some patients with mild tinnitus. The same effects were not seen in patients with mild tinnitus and tinnitus duration between 6 and 12months. Our results are promising initial steps towards identifying invariant neural correlates of tinnitus and indexing differences between subgroups. Keywords: Tinnitus, Resting state functional connectivity, fMRI, Default mode network, Dorsal attention network, Precuneus